Влияние метаболического синдрома на состояние костной ткани у детей - Скромная, Н.Н. (Таврический медико-биологический вестник, 2013)
У статті проведено аналіз публікацій присвячених проблемі метаболічного синдрому та стану
кісткової тканини у дітей. Останнім часом з’явилися дані про те, що метаболічний синдром може
асоціюватися з низькою кістковою масою, про взаємозв’язок і можливих спільних механізмах розвитку
цих патологічних процесів. Показано вплив компонентів метаболічного синдрому на кістковий
метаболізм. The article has given the analyses to those published things which are connected with the problem of
metabolic syndrome and bony tissue in children lately, the date about metabolic syndrome and its association
with low bony mass was published. The information states the fact about interconnection and possible
general mechanisms of development of those pathologic processes. The influence of metabolic syndrome
components to bony metabolism has been revealed.